Shoulder Muscle Activity Through Surface Electromyography and Estimation of Physiological Fatigue Using the T-Fast Test in Patients With Glenohumeral Instability: A Cross-Sectional Study - Ramírez-Pérez, Laura; Cuesta-Vargas, Antonio (Wiley, 2025)
Background and Purpose: Electromyography has been widely used to analyze muscle activation during different tasks to establish standard patterns of muscle activity that allow the establishment of preventive strategies related to each type of motor task. The primary aim was to evaluate the muscle activity of the upper trapezius, lateral deltoid, anterior deltoid, and biceps brachii during analytical movements; and to estimate physiological fatigue from kinematic data obtained during the T‐Fast Test. Methods: This cross‐sectional study was developed at Axarquia Hospital (Spain). The study evaluated 38 adults suffering from glenohumeral instability. Surface electromyography was used to evaluate the electrical activity, timing, and mean frequency change of the muscles around the shoulder. In addition, inertial sensors were used to assess kinematic parameters during the TFast Test. Results: Altered patterns in muscle activity, a delay of 1.48 ± 3.69 s for activation timing, and a mean fatigue value of 18.1% ± 40.46. A significant relationship was found between the mean frequency change of the upper trapezius during flexion and the angular velocity in the Y axis during the 30″ T‐Fast Test (p = 0.044). The mean frequency change of the lateral deltoid during abduction was related to linear acceleration in the Z axis during the 30″ T‐Fast Test (p = 0.026) and 120″ T‐Fast Test (p = 0.009) and angular velocity in the Y axis during the 120″ T‐Fast Test (p = 0.032). Discussion: This study revealed altered muscle activity patterns with high fatigue levels in glenohumeral instability and the great utility of inertial sensors to estimate physiological fatigue. Future research should be developed to determine a cut‐off time for fatigue that helps to stratify the population suffering from glenohumeral instability. Trial Registration: ClinicalTrials.gov Identifier: NCT05443295
Keywords: Fisioterapia; Electromiografía; Cinemática; Músculos; Hombros; Electromyography; Instability; Kinematics; Muscle activity; Shoulder